MEASUREMENT OF THE LEVEL AND ABSORPTION SPECTRUM OF MICROWAVE RADIATION BY BIOLOGICAL TISSUES - Штефура, Юлия; Химичева, Анна; Шевченко, Константин (SWorldJournal, 2020)
This study presents the analysis of the existing methods for assessing the absorption capacity of biological tissues in the millimeter wavelength range. Problems that were encountered during it are shown. A functional diagram of the device, which provides